The acute effects and reproducibility of resistance training fatigue on load-velocity relationship variables - Li, R.; Li, Z.; Zheng, J.; Guo, Y.; Ou, G. (International Journal of Sports Science & Coaching, 2025)
Since the load-velocity relationship was validated as a useful tool for assessing fatigue, its reliability and reproducibility have yet to be established, which are crucial for programming training plans and monitoring athletes` physiological status. Therefore, this study aimed to explore the acute effects of resistance training fatigue on load-velocity (L-V) relationship variables (maximal theoretical force capacity [L0], maximal theoretical velocity capacity [v0], and maximal theoretical power capacity [Aline]) under different set configurations and whether the fatigue was reproducible. Fourteen male athletes performed back squats at 80% of their one repetition maximum under 20% velocity loss across three sets configurations (6, 4, and 3 sets), with each configuration performed twice. L-V relationship variables were established in pre-fatigue and 15 min post-fatigue for all sessions. Fatigue resulted in significant decline in v0(F = 27.084, p < 0.001)and Aline(F = 72.552, p < 0.001), but not in L0 (F = 0.466, p = 0.508). The three set configurations produced similar fatigue levels for all L-V relationship variables. The effects of fatigue on L-V relationship variables were reproducible in all set configurations for all variables (ICC = 0.759, CV = 9.3%). The findings suggest that, under a fixed 20% VL, the acute effects of L-V relationship variables were reproducible from resistance training fatigue, no matter how many training sets were applied. Hence, the L-V relationship variables are a reliable tool to measure acute resistance training fatigue.